2019
DOI: 10.34133/2019/1649427
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Edible Lubricant-Infused Surface with Liquid Residue Reduction Properties

Abstract: Inspired by nature’s water-repellent plants, the superhydrophobic surface (SHS) and the lubricant-infused surface (LIS) possess potentials in various fields of application. In particular, the edible SHS and the edible LIS (ELIS) are suitable for the role of high-valued liquid food residue reduction. In this study, the ELIS was introduced through a facile spray method and direct lubricant infusion. Four types of ELISs were fabricated: carnauba wax with ethyl oleate infusion, carnauba wax with cooking oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…The wax-in-ethanol solutions of carnauba wax (purchased from Shanghai Macklin Biochemical Co. Ltd., China) and beeswax (obtained from Solarbio Science & Technology Co. Ltd., China) were prepared using methods previously reported by our research group but with modifications [33,41]. Specifically, 2 g of carnauba wax and beeswax was separately added into flasks with 200 mL of ethanol (purchased from Rionlon, China).…”
Section: Fabrication Of Edible Hydrophobic Mixed Wax Powdermentioning
confidence: 99%
See 2 more Smart Citations
“…The wax-in-ethanol solutions of carnauba wax (purchased from Shanghai Macklin Biochemical Co. Ltd., China) and beeswax (obtained from Solarbio Science & Technology Co. Ltd., China) were prepared using methods previously reported by our research group but with modifications [33,41]. Specifically, 2 g of carnauba wax and beeswax was separately added into flasks with 200 mL of ethanol (purchased from Rionlon, China).…”
Section: Fabrication Of Edible Hydrophobic Mixed Wax Powdermentioning
confidence: 99%
“…The edible hydrophobic powder was prepared through two stage evaporations of wax-in-ethanol emulsion. As the previously conducted experiment indicated that both the sprayed coatings of emulsion-prepared carnauba wax and beeswax particles could possess superhydrophobicity [33,41], when water droplet is dropped onto the powder with superhydrophobicity and superareophilicity, the particles act as a surfactant at the water-air interface and have the tendency to warp the droplet for surface free energy minimization to form liquid marble (LM). The SEM images in Figs.…”
Section: Fabrication Of Edible Wax Powdermentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the reported studies employed perfluorinated oils [19-21, 23-24, 26, 29-30], essential and vegetable oils [27][28], and silicone oils [22,25] as lubricants to demonstrate the LIS capabilities in food packaging applications. Although perflourinated oils are extensively used, such lubricants release fluorine similar to that of fluorinated coatings and therefore pose considerable health risks [35].…”
Section: Polymer Micro/nano Replication and Lis Preparationmentioning
confidence: 99%
“…Zouaghi et al [21] demonstrated that LIS prepared using hierarchical textures produced through ultrashort laser processing of stainless steel could reduce dairy fouling compared to some reference superhydrophobic surfaces. Several other studies focused on preparing LIS on glass and silicon-based substrates examined their non-wetting properties when in contact with complex liquids [22][23][24][25][26][27]. Although most of these studies involved textured metallic and glass substrates, it should be noted that polymers are predominantly used as food packaging materials.…”
Section: Introductionmentioning
confidence: 99%